Assessing the Threat of Online Scamming–Based Human Trafficking: Transnational Criminal Capacity and National Security Implications in the Myawaddy Case - Santoso, A P (Security Intelligence Terrorism Journal (SITJ), 2026)
Online scamming–based human trafficking has emerged as a complex transnational phenomenon that combines digital deception with coercive exploitation. This research analyzes the threat posed by human trafficking syndicates operating in Myawaddy, Myanmar, by examining their operational intent, capacity, and the vulnerabilities that enable sustained victimization. This study employs a qualitative methodology, drawing data from semi-structured interviews with repatriated Indonesian victims, institutional stakeholders involved in protection and law enforcement, and subject matter experts, complemented by secondary data from international organization reports and scholarly literature. The analysis is framed using Hank Prunckun’s threat assessment and vulnerability assessment framework. The findings indicate that the threat level is high, driven by persistent criminal intent and advanced transnational operational capability, while vulnerabilities remain acute due to economic pressure, limited digital safeguards, normalized online recruitment practices, and gaps in cross-border oversight. From a national security perspective, this threat is non-traditional and multidimensional, affecting human security, political and diplomatic capacity, social resilience, economic stability, and cybersecurity. The study concludes that addressing this threat requires an integrated security response that combines disruption of transnational scam operations with structural efforts to reduce domestic vulnerabilities that sustain exposure to exploitation.